RESEARCH PAPEROptimization of activated sludge storage before RNA isolation - Cydzik-Kwiatkowska, Agnieszka; Wnuk, Marta (BioTechnologia, 2011)
Proper sample storage before RNA isolation is crucial for a reliable assessment of microbial activity in activated sludge. In our studies, different amounts of activated sludge expressed in mg of total suspended solids (TSS) were fixed with a constant volume of RNA later RNA Stabilization Reagent (QIAGEN, Germantown, MD, USA) and stored for 3 or 6 months. The results obtained point out that for the best RNA recovery, 1 mg of activated sludge TSS should be fixed with 33 μl of the RNA later . It was also observed that a longer storage period (6 vs. 3 months) of the activated sludge in RNA later lowered RNA recovery by, on average, 25 ± 15% although bacterial diversity in all samples remained unaltered.